Increased risk of metabolic bone disease in preterms born to preeclamptic mothers: A case-control study - Bezirganoglu, Handan; Karacaglar, Nazmiye Bengu; Kanmaz Kutman, Gozde (Annals of Medical Research, 2023)
Aim: To evaluate if there is an increased risk of metabolic bone disease associated with preeclampsia.Materials and Methods: Preterm infants
Keywords: Metabolic bone disease; Prematurity; Preeclampsia